Ecojustice, equity and ethics: challenges for educational and career guidance - Irving, Barrie Anthony; Liévano, Beatriz Malik (Revista Fuentes, 2019)
In social and environmental terms we live in precarious and uncertain times, where not only the sustainability of the planet rests in the balance, but also that of human existence. Many nation-states around the world talk of the importance of social cohesion, and are aware of the threat of environmental degradation, climate change, and ecological well-being. However, the dominating global policy discourse, particularly championed in the West, is located within a delimiting neo/liberal political framework. With a few noticeable exceptions, the influence of neo/liberal thinking continues to flourish in the contemporary career literature where there has been little deep critical engagement with the discourse of capitalist economics and how these impact human and environmental well-being. Often caught up in market-led discourses and captured by the notion that ‘work sets you free’, educational and career guidance has been located within an uncritical economic frame. Its energies tend to be directed towards the preparation of individuals to make ‘good’ educational and occupational choices, underpinned by the need for ‘clients’ to acquire the skills and competencies demanded by employers (and the economy) (Bengtsson, 2011; Irving, 2018). The disjuncture between educational and career guidance and social and environmental justice (i.e. ecojustice) has rarely been breached. In this article, we seek to disrupt dominant discourses of the market that currently permeates thinking in education by identifying how an ecojustice perspective provides a forward looking and equitable foundation for educational and career guidance.